2010
DOI: 10.1103/physreve.81.011803
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-graining scheme for simulating uniaxial stress-strain response of glassy polymers through molecular dynamics

Abstract: Simulation of the deformation of polymers below their glass transition through molecular dynamics provides an useful route to correlate their molecular architecture to deformation behavior. However, present computational capabilities severely restrict the time and length scales that can be simulated when detailed models of these macromolecules are used. Coarse-graining techniques for macromolecular structures intend to make bigger and longer simulations possible by grouping atoms into superatoms and devising w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…By introducing additional pressure matching scheme, the pressure is found to be reasonably reproduced, but there are competing opinions regarding the reproduction of isothermal compressibility. Carbone et al 61 found that including the so-called ramp correction to the CG non-bonded potentials derived from IBI, the CG FF developed for polyamide 66 can reasonably reproduce the atomistic isothermal compressibility, i.e., at 400k the corresponding CG value is 7.9*10 -7 kPa -1 close to the atomistic one of 2.1*10 -7 kPa -1 , while for PS the resulting CG FF fails to reproduce the correct compressibility with the corresponding CG value being two orders of magnitude higher than the atomistic one. Additionally, a recent work on liquid water indicates that the side effect of the pressure-correction is a strong deviation in the isothermal compressibility and thus the pressure and the liquid isothermal compressibility cannot be reproduced simultaneously through both structure and pressure matching.…”
Section: Isotropic Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…By introducing additional pressure matching scheme, the pressure is found to be reasonably reproduced, but there are competing opinions regarding the reproduction of isothermal compressibility. Carbone et al 61 found that including the so-called ramp correction to the CG non-bonded potentials derived from IBI, the CG FF developed for polyamide 66 can reasonably reproduce the atomistic isothermal compressibility, i.e., at 400k the corresponding CG value is 7.9*10 -7 kPa -1 close to the atomistic one of 2.1*10 -7 kPa -1 , while for PS the resulting CG FF fails to reproduce the correct compressibility with the corresponding CG value being two orders of magnitude higher than the atomistic one. Additionally, a recent work on liquid water indicates that the side effect of the pressure-correction is a strong deviation in the isothermal compressibility and thus the pressure and the liquid isothermal compressibility cannot be reproduced simultaneously through both structure and pressure matching.…”
Section: Isotropic Compressionmentioning
confidence: 99%
“…In a recent work, Rahimi et al showed that for a typical PS CG model with the CG FF parameterized by the pure structure matching method, the resulting Young's modulus is significantly lower than the atomistic simulation data 62. Also, for a similar CG model with the CG FF determining by the multiscale coarse-graining (MS-CG) method, Majumder et al discovered that the CG model greatly overestimates the pressure when the sample is held at the parameterizing temperature and the same volume and such a huge mismatch in the pressure makes a match in the stress or elastic properties impossible 61. Furthermore, by introducing a frictional force through the use of DPD thermostat to slow down the dynamic response of the CG model under strain, Rosch found an improvement of the CG model's ability to match the stress-stain behavior of the underlying atomistic model can be achieved, i.e., the resulting elastic modulus in the CG system is 3.6 Gpa, only about twice as big as the atomistic one (1.7GPa) 12.…”
mentioning
confidence: 99%
“…In coarsening kinetics of binary mixtures such time dependence of the relevant length scale can be described correctly when one considers an off-set in the scaling ansatz [80,[82][83][84]. Similarly, it was later proved to be appropriate for the cluster growth during the collapse of a polymer [36,39].…”
Section: Cluster Growthmentioning
confidence: 97%
“…Argon et al, found that plastic relaxation was induced by repeatable nucleation of shear transformations that leads to dilatancy in polypropylene [18] while the opposite behavior was observed in polycarbonate. [19] Although there have been extensive studies on mechanical behaviors of glassy polymers under plastic deformation via molecular dynamics simulations, [20][21][22][23][24][25] and a few reviews, [7,26,27] the quantitative relationships between deformation dilatancy and plastic relaxation events are yet to be fully understood.…”
Section: Doi: 101002/mats202000063mentioning
confidence: 99%